2001
DOI: 10.1086/321149
|View full text |Cite
|
Sign up to set email alerts
|

Host Galaxies, Obscuration, and Nuclear Structure of Three Nearby Compact Symmetric Objects

Abstract: We present three-band Hubble Space T elescope imaging of three nearby (z ¹ 0.1) compact symmetric objects : 4C 31. 04, 1946]708, and 1146]596. These objects were chosen on the basis of proximity to Earth as well as H I 21 cm line absorption. The inner H-band isophotes of these galaxies are well Ðtted by Nuker models, typical of nearby elliptical galaxies. Each shows a signiÐcant Ñattening in the isophotal proÐle at radii as well as signiÐcant variations in ellipticity and P.A. However, as previous D0A .5, auth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 74 publications
(139 reference statements)
4
46
0
Order By: Relevance
“…The presence of a circumnuclear disk is also supported by HST observations (Perlman et al 2001), which reveal a disk-like dusty feature of somewhat larger scale but similar orientation to the one suggested by Conway. The optical nucleus is also found to have cone-like features well aligned with the radio axis.…”
Section: Introductionsupporting
confidence: 76%
“…The presence of a circumnuclear disk is also supported by HST observations (Perlman et al 2001), which reveal a disk-like dusty feature of somewhat larger scale but similar orientation to the one suggested by Conway. The optical nucleus is also found to have cone-like features well aligned with the radio axis.…”
Section: Introductionsupporting
confidence: 76%
“…For example Perlman et al (2001) have found evidence for old (D108 yr) merging activity in three young compact symmetric object (CSO) radio galaxies and have suggested that the mergers may be related to a delayed onset of radio activity. The parallels with Cen A are obvious.…”
Section: Discussionmentioning
confidence: 99%
“…VLBA (Very Long Baseline Array) images at 5 GHz show a compact core component with hot spots and lobes on either side (Giroletti et al 2003). Spectral line VLBI (Very Long Baseline Interferometer) observations reveal the presence of an edge-on circumnstellar H I disk (Perlman et al 2001). The optical nucleus is also found to have cone-like features well aligned with the radio axis.…”
Section: B2 0116+31mentioning
confidence: 97%